2022
DOI: 10.3389/fcvm.2022.1017209
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the causal association between celiac disease and cardiovascular diseases

Abstract: BackgroundEpidemiological studies have reported inconsistent results of the association between celiac disease (CD) and cardiovascular diseases. Moreover, the causality remains largely unknown. Therefore, we aimed to investigate whether CD is causally associated cardiovascular diseases, including ischemic stroke, large artery stroke, cardioembolic stroke, small vessel stroke, coronary heart disease, myocardial infarction, angina, heart failure, atrial fibrillation, and venous thromboembolism using an mendelian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…. (18) The main limitation of the study is the small number of the patients and controls in the study. Additionally, although all the patients left ventricular systolic function were normal in the study, we did not evaluated the left ventricular diastolic function.…”
Section: Discussionmentioning
confidence: 98%
“…. (18) The main limitation of the study is the small number of the patients and controls in the study. Additionally, although all the patients left ventricular systolic function were normal in the study, we did not evaluated the left ventricular diastolic function.…”
Section: Discussionmentioning
confidence: 98%
“…Primarily, it focuses on a European population, and caution should be exercised in generalizing these ndings to other ethnic groups. Furthermore, as CD is a multifactorial autoimmune disorder, genetic factors account for only a fraction of its pathogenesis [32],and the role of dietary habits and living conditions in the causal relationship between CD and digestive system cancers warrants further investigation. Future studies are needed to explore the mechanisms by which malignancy develops in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the mainstream scientific literature reports an increased CVD risk among celiac patients, on the contrary, studies supporting a null or reduced risk are not very numerous [ 16 , 23 , 24 , 27 , 46 , 52 , 53 ]. In an early prospective multicenter study recruiting 1072 Italian adult celiac patients, Corrao et al reported a nonsignificant reduced cardiovascular risk despite a two-fold increase in overall mortality [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an open cohort study detected a slightly lower cumulative incidence of cardiovascular deaths (35 vs. 51 per 10,000 person years) among 10,825 celiac patients from the UK [ 52 ]. Finally, a Mendelian randomization study aiming to investigate the causal effect of CD on CVD failed to provide evidence supporting a causal association of CD with a number of atherosclerosis-based disorders, including ischemic stroke and peripheral artery disease [ 27 ]. In support, the lack of association between CD and CVD was also described in the meta-analyses of Emilsson et al [ 23 ] and Heikkilä et al [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation